Synthesis and evaluation of hybrid mannich base-tetraoxane derivatives as potent anti-malarial agents - Malita Sarma; Dipak Chetia; Khumanthem Deepak Singh; Zartaj Washmin Banu; Chandrajit Dohutia (International Journal of Pharmacy and Analytical Research, 2016)
In spite of being a promising drug against malaria, artemisinin at present, demands considerable modifications due to increased resistance of malarial parasites towards it. Presence of Mannich base phenol side chain within the tetraoxane scaffold has shown to deliver a new class of hybrid drugs with dual potency agai nst Plasmodium falciparum. Taking this into consideration 5 hybrid chemotypes containing Mannich base as a pharmacophoric group with a tetraoxane core were synthesized and evaluated for anti -malarial activity. Synthesized compounds MS-I and MS-IV showed IC50 values of 0.391 and 0.383 µg/100 µL respectively while rest showed IC 50 values of 0.464, 0.433 and 0.762 µg/100 µL respectively. MS-I and MS-IV were subsequently screened against mutant RKL-2 strain yielding IC50 values of 0.807 and 1.619 µg/100 µL resp ectively.